High Temperature Oxidation, Metal Dusting, Erosion and Corrosion Behavior of Fe-18Cr-21Mn-0.65N Austenitic Stainless Steel - Kumar, Sharvan (IIT(BHU) Varanasi, 2022)
Abstract is available in the attachment.
This thesis is submitted by Sharvan Kumar , Department of Metallurgical Engineering of IIT(BHU),Varanasi under the supervision of Dr. G.S. Mahobia.
Keywords: High Temperature; Oxidation; Metal; Erosion; Austenitic Stainless Steel